Nano-porous NiFeCoCuCrMn / Al3 (NiFeCoCuCrMn) 2 composite electrode as well as preparation method and application of nano-porous NiFeCoCuCrMn / Al3 (NiFeCoCuCrMn) 2 composite electrode
By preparing nanoporous NiFeCoCuCrMn/Al3 (NiFeCoCuCrMn)2 composite electrode, the core-shell structure of high-entropy alloy/high-entropy intermetallic compound was solved, and the problem of slow kinetics of the anode oxygen evolution reaction in the electrocatalytic water decomposition hydrogen production reaction was achieved. Highly efficient catalytic performance of hydrazine hydrate oxidation and hydrogen evolution reaction.
Patent Information
- Application Number
- CN202411844822.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the existing electrocatalytic water decomposition hydrogen production reaction, the oxygen evolution reaction of the anode is slow and requires a high voltage. The theoretical voltage of the hydrazine hydrate oxidation reaction is low, making it difficult to effectively reduce the hydrogen production voltage.
Nanoporous NiFeCoCuCrMn/Al3 (NiFeCoCuCrMn)2 composite electrode was prepared by alloying method and eutectic template dealloyment method to form a high-entropy alloy/high-entropy intermetallic compound core-shell structure electrode material.
The catalytic performance of hydrazine hydrate oxidation and hydrogen evolution reaction is improved, the voltage requirement for hydrogen production reaction is reduced, and the material basis for large-scale hydrogen production is provided.
Smart Images

Figure CN119433574A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, in particular to nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Composite electrode and its preparation method and application. Background Art
[0002] Hydrogen energy is a clean and efficient secondary energy source that can be used as an energy interconnection medium. The electrocatalytic water splitting hydrogen production reaction driven by renewable electricity such as wind power and hydropower is the basis for the green production and efficient utilization of hydrogen energy. The oxygen evolution reaction kinetics at the anode of the electrocatalytic water splitting reaction are slow and require a voltage greater than 1.23V (relative to the reversible hydrogen electrode) to occur, while the theoretical voltage of the hydrazine hydrate oxidation reaction is only -0.33V (relative to the reversible hydrogen electrode), which is expected to replace the oxygen evolution reaction and reduce the voltage of water splitting hydrogen production. The electrocatalytic hydrogen production reaction consisting of the anode hydrazine hydrate oxidation reaction coupled with the cathode hydrogen evolution reaction is a promising hydrogen production pathway. The hydrazine hydrate oxidation reaction is a four-electron transfer process and involves a variety of reaction intermediates. Therefore, it is urgent to construct electrocatalytic materials with multiple active site centers. High entropy alloys have diverse active sites, and the adsorption energy of different reaction intermediates can be regulated by electron transfer or coordination effects caused by the difference in electronegativity between different elements to achieve optimal adsorption / desorption. High entropy intermetallic compounds are composed of multiple elements replacing a certain component in the intermetallic compound, and still have the intrinsic thermodynamic stability of the intermetallic compound. Based on the above considerations, the present disclosure proposes a nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Composite electrode and its preparation method and application. Summary of the invention
[0003] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Composite electrode and its preparation method and application.
[0004] According to a first aspect of the present disclosure, there is provided a nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The method for preparing a composite electrode is characterized by comprising the following steps:
[0005] a. Cleaning the metal: soak and clean the high-purity Ni, Fe, Co, Cu, Cr, and Mn metal sheets with dilute hydrochloric acid, and remove the oxide on the surface of the Al metal wire with a dilute NaOH solution, then clean the Ni, Fe, Co, Cu, Cr, and Mn metal sheets and the Al metal wire with ultrapure water for several times, and finally place the Ni, Fe, Co, Cu, Cr, and Mn metal sheets and the Al metal wire that have been cleaned with ultrapure water in a vacuum drying oven;
[0006] b. Melting alloy ingots: weigh the Ni, Fe, Co, Cu, Cr, Mn, and Al washed with ultrapure water according to the atomic ratio of 15:3:3:3:3:3:70, and the total mass of the above metals is 10-12 g; place the weighed metals in an electric arc furnace, use argon as a protective gas, and melt the alloy 8-10 times, and melt multiple times to obtain an alloy ingot with uniform composition; wait for the alloy ingot to cool to room temperature, open the furnace door and take out the alloy ingot, and the alloy ingot is silvery white;
[0007] c. Preparation of columnar alloy by directional solidification method: grinding the oxide layer on the surface of the alloy ingot with sandpaper, cutting the alloy ingot into small alloy ingots with a size less than 9 mm, placing the small alloy ingot in a crucible tube of a directional solidification device, heating it to 1500°C in an argon atmosphere at a heating rate of 10°C / min, keeping it at a preset temperature for 10 minutes, stretching the small alloy ingot at a preset stretching speed, and the stretching stroke is 10 cm; after the stretching is completed and the temperature drops to room temperature, taking out the small alloy ingot, the small alloy ingot has a columnar appearance with a diameter of 1 cm;
[0008] d. Preparing alloy flakes: cutting the columnar alloy ingots with a diamond wire cutting machine to obtain alloy flakes of a preset size;
[0009] e. Chemical dealloying: placing the alloy disc at a preset temperature and N 2 The alloy disc was corroded in a saturated 6M KOH solution. After a certain period of time, when no bubbles were generated on the surface of the alloy disc, the alloy disc was washed with ultrapure water for several times to obtain a nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Composite electrode.
[0010] Preferably, the precursor alloy composition of the alloy ingot in step b is Ni 15 Fe 3 Co 3 Cu 3 Cr 3 Mn 3 Al 70 (at%).
[0011] Preferably, in the preparation of columnar alloy by directional solidification method described in step c, the preset temperature is 1500° C., and the preset stretching speed is 100 μm / s.
[0012] Preferably, the alloy disc of preset size in step d has a diameter of 1 cm and a thickness of 400 μm.
[0013] Preferably, in step e, the alloy disc is placed at 70°C and N 2 The corrosion was carried out in a saturated 6M KOH solution for 5 hours.
[0014] According to a second aspect of the present disclosure, there is provided a nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Composite electrode.
[0015] According to a third aspect of the present disclosure, there is provided a nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The application of the composite electrode is characterized in that the composite electrode is used as a hydrazine hydrate oxidation reaction electrode and a hydrogen evolution reaction electrode.
[0016] The principle of the disclosed technical solution is:
[0017] The alloy method and eutectic template dealloying method are used for preparation, which has simple process and can be operated on a large scale. First, high-purity metals Ni, Fe, Co, Cu, Cr, Mn, and Al are smelted into precursor alloy ingot Ni in an electric arc furnace. 15 Fe 3 Co 3 Cu 3 Cr 3 Mn 3 Al 70 The alloy is stretched into a cylindrical alloy using a directional solidification device. The precursor alloy is composed of Al, Al 3 (NiFeCoCuCrMn) 2 、Al 13 Fe 4 、Al 9 Co 2 , CuAl 2 、Al 6 Mn、Al 3 Ni and Al 13 Cr 2 Then it is cut into thin slices by wire cutting equipment, and finally Al is corroded away by alkali solution through chemical dealloying to form nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn)2 Composite electrode. During the chemical dealloying process, the Al in the Al-rich intermetallic compound is corroded to form small holes. Fe, Co, Cu, Cr, and Mn are 3 (NiFeCoCuCrMn) 2 The high entropy alloy NiFeCoCuCrMn is diffused on the ligament surface, thus forming a high entropy intermetallic compound / high entropy alloy core-shell structure electrode material.
[0018] The beneficial effects of the disclosed technical solution are:
[0019] The core-shell structure electrode material disclosed in the present invention has a porous structure, and the pores are conducive to the mass transfer of electrolyte and gas molecules, and increase the specific surface area of the material, increase the accessibility of electrocatalytic active sites, expose more active sites in the electrolyte, and the three-dimensional interconnected Ni network is conducive to electron transfer during the catalytic reaction. 3 (NiFeCoCuCrMn) 2 It has thermodynamic stability and acts as a core to produce strain on the surface high entropy alloy NiFeCoCuCrMn, thereby regulating the adsorption capacity of the surface high entropy alloy to adsorbate; the high entropy alloy as the shell has multiple active site centers, which properly adsorbs a variety of reactants, reaction intermediates and products, thereby improving the reaction kinetics. 3 (NiFeCoCuCrMn) 2 High entropy alloy / high entropy intermetallic compound composite electrode materials have excellent catalytic performance in hydrazine hydrate oxidation and hydrogen evolution reactions, providing a material basis for large-scale hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and other features, advantages and aspects of the embodiments of the present disclosure will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. The accompanying drawings are used to better understand the present solution and do not constitute a limitation of the present disclosure. In the accompanying drawings, the same or similar reference numerals represent the same or similar elements, among which:
[0021] Figure 1 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Scanning electron microscope (SEM) images of
[0022] Figure 2 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Energy dispersive spectrometer (EDS) diagram;
[0023] Figure 3 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 X-ray diffraction (XRD) pattern;
[0024] Figure 4 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 High-resolution transmission electron microscopy (HRTEM) images;
[0025] Figure 5 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 TEM images and elemental distribution maps;
[0026] Figure 6 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 In 1MKOH and 0.1MN 2 H 4 Polarization curve of hydrazine hydrate oxidation reaction in mixed electrolyte;
[0027] Figure 7 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Tafel diagram of hydrazine hydrate oxidation reaction;
[0028] Figure 8 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Polarization curve of hydrogen evolution reaction in 1M KOH electrolyte;
[0029] Fig. 9 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Tafel diagram of hydrogen evolution reaction;
[0030] Fig.10 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2Polarization curve of the assembled water electrolysis hydrogen production device, the anolyte is 1MKOH and 0.1MN 2 H 4 Mixed solution, catholyte is 1MKOH;
[0031] Fig.11 , the disclosed embodiment of the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Stability of the assembled water electrolysis hydrogen production device. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0033] Example 1
[0034] A nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The preparation method of the composite electrode comprises the following steps:
[0035] 1) Cleaning the metal: soaking and cleaning the high-purity Ni, Fe, Co, Cu, Cr, and Mn metal sheets with dilute hydrochloric acid, and removing the oxide on the surface of the Al metal wire with a dilute NaOH solution, and then cleaning the Ni, Fe, Co, Cu, Cr, and Mn metal sheets and the Al metal wire with ultrapure water for several times, and finally placing the Ni, Fe, Co, Cu, Cr, and Mn metal sheets and the Al metal wire that have been cleaned with ultrapure water in a vacuum drying oven;
[0036] 2) Melting alloy ingots: weigh the Ni, Fe, Co, Cu, Cr, Mn, and Al washed with ultrapure water according to an atomic ratio of 15:3:3:3:3:3:70, and the total mass of the above metals is 10 to 12 g; place the weighed metals in an electric arc furnace, use argon as a protective gas, and melt the alloy 8 to 10 times, and melt multiple times to obtain an alloy ingot with uniform composition; wait for the alloy ingot to cool to room temperature, open the furnace door and take out the alloy ingot, and the alloy ingot is silvery white;
[0037] 3) Preparation of columnar alloy by directional solidification method: grinding the oxide layer on the surface of the alloy ingot with sandpaper, cutting the alloy ingot into small alloy ingots with a size of less than 9 mm, placing the small alloy ingot in a crucible tube of a directional solidification equipment, heating it to 1500°C in an argon atmosphere, with a heating rate of 10°C / min, keeping it at 1500°C for 10 minutes, stretching the small alloy ingot at a speed of 100 μm / s, and the stretching stroke is 10 cm; after the stretching is completed and the temperature drops to room temperature, take out the small alloy ingot, and the appearance of the small alloy ingot is a column with a diameter of 1 cm;
[0038] 4) preparing alloy flakes: cutting the columnar alloy ingots with a diamond wire cutting machine to obtain alloy flakes with a diameter of 1 cm and a thickness of 400 μm;
[0039] 5) Chemical dealloying: The alloy disc is placed at 70°C and N 2 The alloy disc was corroded in a saturated 6M KOH solution. After a certain period of time, when no bubbles were generated on the surface of the alloy disc, the alloy disc was washed with ultrapure water for several times to obtain a nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Composite electrode materials.
[0040] The morphology and structure characterization results of the composite electrode materials are as follows:
[0041] Figure 1 Nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 SEM images of the composite electrodes. Figure 2 The transmission electron microscope image of the electrode shows that the electrode has a nanoporous structure with a pore size of about 3 to 5 nm. The special pores promote the mass transfer of electrolyte and gas molecules, and increase the specific surface area of the electrode material, exposing more active sites in the electrolyte. The three-dimensional interconnected Ni network is conducive to electron transfer during the catalytic reaction. Figure 3 In the XRD spectrum, the characteristic peaks at 25.2°, 31.2°, 40.8°, 45.0°, 48.5°, and 65.3° correspond to Al 3 Ni 2 The (100), (101), (110), (102), (111), and (202) crystal planes of the NiFeCoCuCrMn high entropy alloy surface are relatively low, and the XRD peaks are not obvious. 3 (NiFeCoCuCrMn) 2 The characteristic peaks of the composite electrode relative to Al 3 (NiCu) 2 / NiCu characteristic peak shifts to high angles, indicating that FeCoCuCrMn 3 Ni 2 Replaced part of Ni in the . Figure 4 The high-resolution transmission electron microscopy images further characterized the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The core-shell structure of the composite electrode. Figure 5 As shown in the transmission electron microscope image and the corresponding element distribution results, Fe, Co, Cu, Cr, Mn, and Al are evenly distributed on the Ni ligaments.
[0042] Example 2
[0043] The hydrazine hydrate oxidation reaction performance of the composite electrode material obtained in Example 1 was tested in a three-electrode system. 2 H 4 In the mixed solution, nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The composite electrode material is used as the working electrode, the carbon rod is used as the counter electrode, and the Ag / AgCl electrode is used as the reference electrode. The specific test process is as follows:
[0044] 1) In the voltage range of -0.05 to 0.15 V (relative to the reversible hydrogen electrode), the -1 The polarization curve of hydrazine hydrate oxidation reaction was tested at a scanning rate of
[0045] 2) Test its impedance spectrum at 0V, with an amplitude of 5mV and a frequency of 10mHz to 100kHz;
[0046] Nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The characterization results of the hydrogen evolution reaction performance of the electrode material are as follows:
[0047] Figure 6 Compared with nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 Polarization curves of hydrazine hydrate oxidation reaction of composite electrode and nanoporous NiFeCoCuAl, NiCrMn and NiCuAl electrodes. At a potential of 100mV, Al 3 (NiFeCoCuCrMn) 2 / NiFeCoCuCrMn electrode can reach ~1.12Acm -2 The current density is much higher than that of NiCrMnAl (~0.62Acm-2 )、NiFeCoCuAl、(~0.32Acm -2 )、NiCuAl(~0.26Acm -2 ) The current density of the electrode. In addition, Figure 7 As shown, nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The Tafel slope of the electrode is as low as ~17mV dec -1 , which is significantly lower than other comparative electrode materials, indicating that the electrode has excellent hydrazine hydrate oxidation reaction performance.
[0048] Example 3
[0049] The hydrogen evolution reaction performance of the composite electrode material obtained in Example 1 was tested in 1M KOH. The specific testing process is as follows:
[0050] 1) Test the polarization curve of hydrogen evolution reaction, the voltage range is 0~-0.40V (relative to the reversible hydrogen electrode), and the scanning speed is 1mV s -1 ;
[0051] 2) Measure its impedance at -0.1V (relative to the reversible hydrogen electrode), with an amplitude of 5mV and a frequency of 10mHz to 100kHz;
[0052] Nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The results of characterization of the hydrogen evolution reaction performance of the composite electrode are as follows:
[0053] Figure 8 Compared with nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 , NiFeCoCuAl, NiCuAl, Ni electrode hydrogen evolution reaction polarization curves. NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 At a voltage of 0.2V, it can reach ~1.77Acm -2 The current density is much higher than that of NiFeCoCuAl (~0.96Acm -2 ),NiCuAl(~0.35A cm -2 ) and Ni (~0.14 mA cm -2 ). In addition, Fig. 9 As shown, nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2The Tafel slope of the hydrogen evolution reaction is as low as 41mV dec -1 , which is much smaller than other comparative electrodes, indicating that the composite electrode has excellent reaction kinetics.
[0054] Example 4
[0055] The performance of the electrolytic cell hydrogen production system assembled with the composite electrode material obtained in Example 1 was tested. The specific test process is as follows:
[0056] 1) The polarization curve of the electrolytic cell hydrogen production system composed of the composite electrode as cathode and anode was tested, with a voltage range of 0 to 1.0 V and a scan rate of 1 mV s -1 ;
[0057] 2) The stability of the composite electrode was tested at a constant potential of 0.25 V for 1000 hours.
[0058] Fig.10 Demonstrated nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The assembled electrolytic cell only requires 0.9V to drive 0.5A cm -2 of current density. Fig.11 It shows that nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The current density is stable at 120 mA cm at 0.25 V. -2 The current density shows that the electrode has excellent electrochemical stability.
[0059] In summary, the nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 It has a nanoporous structure with a pore size of about 3 to 5 nm. The special pores promote the mass transfer of electrolyte and gas molecules, increase the specific surface area of the electrode material, and expose more active sites in the electrolyte. The surface high entropy alloy has multiple active site centers, which can regulate the adsorption energy of intermediates in the hydrogen evolution reaction and hydrazine hydrate oxidation reaction, thereby achieving optimal adsorption and improving reaction kinetics. Therefore, nanoporous NiFeCoCuCrMn / Al 3 (NiFeCoCuCrMn) 2 The composite electrode has excellent performance in hydrazine hydrate oxidation reaction and hydrogen evolution reaction, providing a material basis for the large-scale commercial application of hydrogen production by coupling cathode hydrogen evolution reaction with anode hydrazine hydrate oxidation reaction.
[0060] The above embodiments are preferred implementation modes of the present disclosure, but the implementation modes of the present disclosure are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present disclosure should be equivalent replacement methods and are included in the protection scope of the present disclosure.
Claims
1. A method for preparing a nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode, characterized in that: The following steps are involved: a. Cleaning the metal: soak and clean the high-purity Ni, Fe, Co, Cu, Cr, and Mn metal sheets with dilute hydrochloric acid, and remove the oxide on the surface of the Al metal wire with a dilute NaOH solution, then clean the Ni, Fe, Co, Cu, Cr, and Mn metal sheets and the Al metal wire with ultrapure water for several times, and finally place the Ni, Fe, Co, Cu, Cr, and Mn metal sheets and the Al metal wire that have been cleaned with ultrapure water in a vacuum drying oven; b. Melting alloy ingots: weigh the Ni, Fe, Co, Cu, Cr, Mn, and Al washed with ultrapure water according to the atomic ratio of 15:3:3:3:3:3:70, and the total mass of the above metals is 10-12 g; place the weighed metals in an electric arc furnace, use argon as a protective gas, and melt the alloy 8-10 times, and melt multiple times to obtain an alloy ingot with uniform composition; wait for the alloy ingot to cool to room temperature, open the furnace door and take out the alloy ingot, and the alloy ingot is silvery white; c. Preparation of columnar alloy by directional solidification method: grinding the oxide layer on the surface of the alloy ingot with sandpaper, cutting the alloy ingot into small alloy ingots with a size of less than 9 mm, placing the small alloy ingot in a crucible tube of a directional solidification device, heating it to 1500°C under an argon atmosphere, with a heating rate of 10°C / min, keeping it at a preset insulation temperature for 10 minutes, stretching the small alloy ingot at a preset stretching speed, and the stretching stroke is 10 cm; after the stretching is completed and the temperature drops to room temperature, taking out the small alloy ingot, the small alloy ingot has a columnar appearance with a diameter of 1 cm; d. Preparing alloy flakes: cutting the columnar alloy ingots with a diamond wire cutting machine to obtain alloy flakes of a preset size; e. Chemical dealloying: The alloy disc is placed in a 6M KOH solution saturated with N2 at a preset corrosion temperature for corrosion. After a certain period of corrosion, when no bubbles are generated on the surface of the alloy disc, the alloy disc is washed with ultrapure water for multiple times to obtain a nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode.
2. The method for preparing the nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode according to claim 1, characterized in that: The precursor alloy composition of the alloy ingot in step b is Ni 15 Fe3Co3Cu3Cr3Mn3Al 70 (at%).
3. The method for preparing the nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode according to claim 1, characterized in that: In the preparation of columnar alloy by directional solidification method described in step c, the preset holding temperature is 1500° C., and the preset stretching speed is 100 μm / s.
4. The method for preparing the nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode according to claim 1, characterized in that: The alloy disc of the preset size in step d has a diameter of 1 cm and a thickness of 400 μm.
5. The method for preparing the nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode according to claim 1, characterized in that: In step e, the alloy disc is placed in a 6M KOH solution saturated with N2 at 70° C. for corrosion, and the corrosion time is 5 hours.
6. A nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode obtained according to the preparation method according to any one of claims 1-5.
7. Use of the nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode according to claim 6, characterized in that: The composite electrode is used as a hydrazine hydrate oxidation reaction electrode and a hydrogen evolution reaction electrode.
Citation Information
Patent Citations
High-strength and high-conductivity CuAg alloy material and preparation method thereof
CN101643866A
Directional solidification smelting device and method for refractory high-entropy alloy
CN110514004A
Preparation method and application of multi-component intermetallic compound nanoparticles on layered metal network
CN115652328A
Multi-component spinel porous nanowire as well as preparation method and application thereof
CN116117129A
Multi-component alloy electrolyzed water catalyst with body-centered cubic structure as well as preparation method and application of multi-component alloy electrolyzed water catalyst
CN118086920A